Binary nano-enhanced phase change materials (BNePCMs) integrated serpentine flow based photovoltaic thermal system: A new approach towards performance enhancement - Ali Laghari, Imtiaz; Pandey, A. K.; Mahendran, Samykano; Rajamony, Reji Kumar; Bhutto, Yasir Ali; Soomro, Abdul Hameed; K., Kadirgama; Tyagi, V. V. (Elsevier Ltd, 2024)
Photovoltaic thermal systems (PVT) are widely acknowledged as solar technology that effectively produces both electrical and thermal energy. Nevertheless, the performance of photovoltaic (PV) systems is significantly affected by elevated temperatures of solar cells. Phase change materials (PCMs) are a class of substances that possess the ability to store and release latent heat. However, PCMs have inadequate thermo-physical characteristics, which may be altered via the incorporation of different nanoparticles. Herein, binary nanoparticles (Titanium oxide and Graphene) enhanced PCM (Paraffin Wax) is integrated with the PVT system to improve its thermal and electrical performance. The present study utilized a unique two side serpentine flow absorber to effectively extract heat energy. The effectiveness of the created PVT system was evaluated using three mass flow rates (0.3, 0.5, and 0.7 LPM). Further, as prepared BNePCM having thermal conductivity and latent heat of 179 % and 10 % higher than that of base PCM, respectively was integrated with PVT system. The energy analysis was used to assess the heat transfer and electrical power output. As per results, at optimum flow rate of 0.3 LPM; the overall energy efficiencies found were 80.49 %, 82.45 %, and 83.65 %, respectively for the PVT, PVT-PCM, and PVT-NePCM systems. Furthermore, the PVT-NePCM system exhibited an electrical output of 46.88 W, which is a significant rise of 10.6 W compared to PV system. Therefore, study will be useful for the applications in preheated water for low and medium temperature range, and cooling applications of electronic devices.